1997
DOI: 10.1017/s0031182097001686
|View full text |Cite
|
Sign up to set email alerts
|

Different Babesia canis isolates, different diseases

Abstract: Using surface immunofluorescence isolate-specific antigens were detected on the membrane of erythrocytes infected with Babesia parasites. In addition, the strains reacted differently with Plasmagel in that the European isolate (B.c. canis) could be purified on Plasmagel effectively, whereas infected erythrocytes of the South-African isolate (B.c. rossi) could not. Experimental infection of dogs with Babesia canis isolates from geographically different areas revealed different pathology. The European isolate ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
55
0
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 9 publications
2
55
0
2
Order By: Relevance
“…During the observation periods before and after antibabesial therapy, no significant PT differences compared to the healthy control group were observed. Schetters et al (1997) reported that there were no statistically significant effects on prothrombin and thrombin times during the infection period, which was similar to what is reported here.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…During the observation periods before and after antibabesial therapy, no significant PT differences compared to the healthy control group were observed. Schetters et al (1997) reported that there were no statistically significant effects on prothrombin and thrombin times during the infection period, which was similar to what is reported here.…”
Section: Discussionsupporting
confidence: 90%
“…There were no statistically significant differences in the APTT values between treatment and control groups on days 0 and 1. In contrast, Schetters et al (1997) demonstrated that there was an increase in the APTT at the time parasites were detected in the peripheral blood. In this report we demonstrated that the APTT levels were reduced on days 2 and 3 after treatment compared to the control group.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Earlier results by Schetters et al (14) have shown that in canine babesiosis, which is characterised by erythrocyte retention, the disease is correlated with the effects on the coagulation system, in contrast to infections characterised by exponentially developing parasitaemia, where the disease is correlated with the peripheral parasitaemia. Vaccination appears to prime Th-cells that assist in the generation of antibodies against SPA, which interfere with the trigger of this pathological process (14). The clinical picture of babesiosis largely depends on the systems and organs within which SPA-induced pathological reactions take place (11,(15)(16)(17).…”
Section: Discussionmentioning
confidence: 92%
“…[2,[4][5][6] . Perakut, akut, kronik ve subklinik seyir gösteren kanin babesiosis'de klinik belirtiler tür, vektör, ırk, yaş ve immun duruma göre değişebilmektedir [1][2][3][6][7][8][9][10][11] .…”
unclassified